2017
DOI: 10.1364/oe.25.000202
|View full text |Cite
|
Sign up to set email alerts
|

Information gain versus interference in Bohr’s principle of complementarity

Abstract: Based on modern quantum measurement theory, we use Zurek's "triple model" to study, from the viewpoint of quantum information theory, the wave and particle nature of a photon in a symmetric Mach-Zehnder interferometer. In the process of quantum measurement, the state of both the system and the detector is not an entangled state but a correlated state. We find that the information gain about the photon is related to the correlations (including classical and quantum correlations) between the photon and the detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Liu et al [39] have demonstrated that D(ρ QD 2 ) and V do not satisfy the complementarity when S x = − cos β = 0 and the input particle is in pure state. For the more general case we discuss in this section, when the final state of the particle and the WPD is in mixed state, the…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [39] have demonstrated that D(ρ QD 2 ) and V do not satisfy the complementarity when S x = − cos β = 0 and the input particle is in pure state. For the more general case we discuss in this section, when the final state of the particle and the WPD is in mixed state, the…”
Section: Discussionmentioning
confidence: 99%
“…Most of the CV-QKD were conducted while splitting signal and LO as Mach-Zehnder interferometer's two arms [15][16][17]. Atmospheric scattering adds difficulty to synchronization in free space for the two beams, and it's also hard for an accurate interference of them at Bob's side.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous-variable QKD (CV-QKD), as one of the implementation schemes of QKD, possesses several advantages over DV-QKD: easier implementation [9][10][11] and lower cost [12][13][14], etc. Most of the CV-QKD systems were performed while splitting signal and LO as Mach-Zehnder interferometer's two arms [15][16][17]. Atmospheric scattering adds difficulty to synchronization of the two beams in free space, and it's also hard for an accurate interference of them at Bob's side.…”
Section: Introductionmentioning
confidence: 99%
“…The arrangement rules out a hidden-variable theory, which suggests that the photon may determine, in advance, which behavior, wave or particle, to exhibit through a hidden variable. [4][5][6][7][8][9][10][11] Recently, a quantum delayed-choice experiment, where BS 2 is engineered to be in a quantum superposition of being present and absent, has been proposed. 12 Such a version allows a single system to be in a quantum superposition of a wave and a particle, so that both behaviors can be observed in a single measurement apparatus at the same time.…”
Section: Introductionmentioning
confidence: 99%